Knowledge and attitude of indian population toward "self-perceived halitosis" - Saurabh Goel; Girish Chaudhary; D S Kalsi; Sumit Bansal; Deepali Mahajan (Wolters Kluwer Medknow Publications, 2017)
Aims: The aim of this study was to assess the level of knowledge and attitude of Indian population toward self-perceived halitosis, about its possible causes, available treatments, its influence on social relations and level of confidence. Materials and Methods: The questionnaire was distributed among 200 people in the outpatient department of Dental Hospital. It had four sections that included sociodemographic data, presence or absence of medical conditions and habits, knowledge about causes and treatment of malodor, oral hygiene practices, whether the subject had halitosis and measures employed to manage the condition, its influence on social relations, and level of confidence. Statistical Analysis Used: Chi-square test. Results: A total of 200 subjects were participated in the study. The prevalence of self-perceived halitosis was 52.5%. There was a significant association between knowledge about causes such as certain foods (P = 0.0004) and tongue coating (P = 0.002) with self-perceived malodor. There were significant associations between self-perceived halitosis and hesitation to talk to other people (P = 0.002) and uneasy feeling when someone was nearby (P = 0.010). Most of the respondents (61.25%) were not willing to visit a dentist or a physician for the condition. Conclusions: The Indian population lacked the knowledge regarding self-perceived halitosis. They had a negative attitude toward it as well.